VOCATIONAL DYNAMICS OF THE SPIRITUAL EXERCISES - Rojas, Hernán (2023)
In the context of the 500th anniversary of the experience that inspired the Spiritual Exercises of Ignatius of Loyola, the present article approaches the Exercises from their vocational dynamic. To do so, vocation is presented, in the first part, as an inclusive, integrating and dynamic concept that seeks to articulate identity, personal freedom and God’s call. In the second part, some dimensions of the Exercises and of the anthropology that underlies them are presented. The vocational dynamic is shown in the personal encounter of the retreatant with God as their own origin and destiny, in the recognition and valuing of human freedom, in the communitarian dimension of vocational discernment and in the personal relationship with Jesus as model and teacher for their own vocation. It thus offers a transversal perspective for contemplating the Spiritual Exercises that can be very relevant to contemporary culture. KEYWORDS: Vocation. Spiritual Exercises. Ignatius of Loyola. Karl Rahner.